Differences in microporous fractal characteristics of tight sandstones of different diagenetic facies: Chang 6 reservoirs of the Triassic Yanchang Formation in the western Ordos Basin, China - Chen, Dayou; Zhao, Huanhuan; Zheng, Feifei; Wang, Yizhe; Ma, Dongxu; Jia, Qianqian; Han, Feng; Gao, Wenbo (Frontiers in Earth Science, 2025)
IntroductionMicroporous structures of tight sandstones show diverse fractal features in different diagenetic facies.MethodsExperimental tests such as cast thin sections, scanning electron microscopy, high-pressure mercury pressure, and low-temperature nitrogen adsorption were applied to clarify the pore fractal differences between various diagenetic facies. The diagenesis, pore types, and pore distribution characteristics of typical tight sandstone samples from the Chang 6 reservoir of the Triassic Yanchang Formation in the Ordos Basin, China, are systematically analyzed. Furthermore, fractal theory is applied to investigate the differences in pore fractal characteristics among various diagenetic facies, as well as the controlling factors influencing these differences.ResultsThe results show that within the study area, we have meticulously divided the diagenetic facies into four main categories: strong compaction facies, carbonate cementation facies, clay mineral cementation facies, weak cementation, and strong dissolution facies. Samples from different diagenetic facies exhibit significant variability in pore size distribution, and the microscopic pores structure is multifractal, with different fractal dimensions for different aperture ranges. The highest fractal dimension of different pores in strong compaction facies indicates strong compaction facies pore surface roughness. The pores are not regular enough and are unfavorable to the storage and infiltration of natural gas in the pores, followed by the carbonate cementation facies and the clay mineral cementation facies. The weak cementation and strong dissolution facies have a low fractal dimension. The pores are relatively more regular, which is more favorable to the storage and infiltration of the pores. Mineral compositions, reservoir properties, and sedimentary facies influence the pore fractal of the tight sandstone in the study area.DiscussionThis study reveals the relationship between diagenetic facies and pore fractals in tight sandstone reservoirs. The study is significant for exploring and developing tight oil in the study area.